ASEAN Economic Community : a model for Asia-wide regional integration? - Aflouk, Nabil 1979-; Witada Anukoonwattaka; Athukorala, Premachandra 1951-; Cabasset Semedo, Christine 1962-; Chaponnière, Jean Raphaël 1946-2022; Jetin, Bruno; Mikić, Mia 1956- (England : Palgrave Macmillan, 2016)
The launch of the ASEAN Economic Community raises key issues: the deepening of regional trade and the associated problem of exchange rate management. This volume questions the capacity of a shallow institution to deal with complex impacts on employment and inequality. Contributors analyze ASEAN's potential and weakness in readable terms.
La función de autores fue determinada por el catalogador
Keywords: ASEAN Economic Community; ASIA SUDESTE -- INTEGRACIÓN ECONÓMICA; ASIA SUDESTE -- COMERCIO